2020
DOI: 10.1101/2020.03.08.20030742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating epidemiological and genetic data with different sampling intensities into a dynamic model of respiratory syncytial virus transmission

Abstract: Background: Respiratory syncytial virus (RSV) is responsible for a significant burden of acute respiratory illness in children under 5 years old. Prior to rolling out any vaccination program, identification of the source of infant infections could further guide vaccination strategies. Methods: We extended a dynamic model calibrated at the individual host level initially fit to social-temporal data on shedding patterns to include whole genome sequencing data available at a lower sampling intensity. Results: I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…Our study found that RSV infection was common in hospitalized children of different ages; the infection most commonly occurred in children<6 months old (45.3%), and the proportion of male children (71.9%) was higher than that of female children (28.1%), which coincides with the results presented by Kombe et al 10 Li et al 11 and Zhu et al 12 RSV is the most common pathogen causing pneumonia. 13 Our study found that 76.6% of children with RSV infection had pneumonia.…”
Section: Discussionsupporting
confidence: 91%
“…Our study found that RSV infection was common in hospitalized children of different ages; the infection most commonly occurred in children<6 months old (45.3%), and the proportion of male children (71.9%) was higher than that of female children (28.1%), which coincides with the results presented by Kombe et al 10 Li et al 11 and Zhu et al 12 RSV is the most common pathogen causing pneumonia. 13 Our study found that 76.6% of children with RSV infection had pneumonia.…”
Section: Discussionsupporting
confidence: 91%
“…This profile is not surprising; for instance, it is well known that majority of transplacental transfer of IgG occurs during the third trimester of pregnancy and that preterm newborns have a compromised passive immunity 27–29 . Furthermore, multiparous mothers are likely to have been exposed to RSV through household transmission from a co‐occupant aged between 2 and 13 years, 30 as well as those delivering at the end of the epidemic season. These factors are also known to be risk factors for severe RSV infection 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…In outbreaks with multiple infected that are epidemiologically linked, finding the most likely transmission route or probable transmission source for each case might prove challenging, and even more so in larger outbreaks. Many different approaches to this have been proposed and have been evaluated to be more efficient than phylogenetic analysis alone [13][14][15]. To establish a probable source of transmission to each secondary case, we first selected transmissions, closest to the expected average serial interval between the expected onset of disease of the two cases.…”
Section: Study Design and Definitionsmentioning
confidence: 99%